(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Serum alpha-fetoprotein (AFP) has long been used to complement imaging tests in the screening and diagnosis of hepatocellular carcinoma (HCC), its utility as a predictive marker of long-term risk for HCC in HBV patients is contentious. Objective: The current study is aimed to assess the serum alpha-fetoprotein with the tumor character and HBV status of HCC to assess its resectability. Methods: This was a single-center, cross-sectional study done from September 2020 to August 2021 at the department of Hepatobiliary, pancreatic, and liver transplantation surgery at BSMMU. A total of 27 HCC patients who met the inclusion criteria were enrolled in the study. Clinical, laboratory, and imaging findings were obtained using a standardized data collecting sheet with the patients’ informed agreement. AFP was measured by automated chemiluminescence analyzer (LIAISON XL, DiaSorin, Italy) in the Department of Biochemistry & Molecular Biology, BSMMU. Statistical analyses were performed using SPSS version 22. Quantitative variables were expressed as mean standard deviation and examined using an unpaired t-test. The qualitative data were represented by frequencies and percentages, and the Chi-Square test and Fisher exact test (where applicable) were used to determine any association. The statistical tests were conducted with a 95% confidence interval, and P<0.05 was deemed statistically significant. Results: Majority of the tumors were single and located in the right lobe. Local extension and distant metastasis were preset in unresectable patients of group 2.Hepatitis B virus was positive in 16 (59.3%) patients and DNA was detectable in 8 (29.6%) patients. HBV positivity and detectable HBV DNA was significantly associated with poor resectable status in group 2 but insignificant in group 1. Conclusions: In this study, the overall resectability was 37%. HBV positive HCC patients are significantly associated with poor resectability when serum AFP is raised and it would be more indicative when HBV DNA is detected. TAJ 2023; 36: No-2: 111-119